Everyday limits to adaptation. Issue 1 (7th January 2022) - Henrique, Karen Paiva; Tschakert, Petra
Abstract: Adaptation to climate change, in terms of both academic and policy debates, has been treated predominantly as a local issue. This scalar focus points towards local agency as well as the contested responsibilization of local actors and potential disconnects with higher-level dynamics. While there are growing calls for individuals to take charge of their own lives against mounting climatic forces, little is known about the day-to-day actions people take, the many hurdles, barriers, and limits they encounter in their adaptation choices, and the trade-offs they consider envisaging the future. To address this gap, this article draws on 80+ interviews with urban and rural residents in Western Australia to offer a nuanced analysis of everyday climate adaptation and its limits. Our findings demonstrate that participants are facing significant adaptation barriers and that, for many, these barriers already constitute limits to what they can do to protect what they value most. They also make visible how gender, age, and socioeconomic status shape individual preferences, choices, and impediments, revealing compounding layers of disadvantage and differential vulnerability. We argue that slow and reflexive research is needed to understand what adaptation limits matter and to whom and identify opportunities to harness and support local action. Only then will we be able to surmount preconceived neoliberal ideals of the self-sufficient, resilient subject, engage meaningfully with ontological pluralism, and contribute to the re-politicization of adaptation decision-making.